Didactical design to overcome learning obstacles in cuboid volume - Jamilah, Jamilah; Priskila, Priskila; Oktaviana, Dwi (Universitas Hamzanwadi, 2024)
This study aims to produce an empirical didactic design designed to overcome didactic barriers experienced by students on beam volume material. Didactical design research is a design in this study that contains three stages of analysis, namely prospective analysis, metapedadidactic analysis, and retrospective analysis. 25 9th-grade junior high school students and one mathematics teacher were selected using purposive sampling techniques to become subjects. Observation, tests using diagnostic tests, and interviews are techniques in data collection. The collected data is analysed and interpreted qualitatively using interpretive and critical paradigms. The results of this study show that through three stages of analysis, an empirical didactic design was obtained that contains four didactic situations: action situations, formulation situations, validation situations, and institutionalisation situations. However, the limitations of presenting problems in institutionalisation situations have an impact on the occurrence of other learning barriers, namely epistemological concepts. Thus, this limitation becomes an improvement material in empirical didactic design.